Reducing the Digital Divide: Distribution of Technology to Increase Access to Pediatric Specialty Care via Telehealth During the COVID-19 Pandemic - Brianne Gilkes; Anna Ditkoff Dorsey; Erin Jones; Christina E. Love; Kimberly Milla; Jennifer Crockett; Jacqueline Stone; Andrew T. Zabel (Telemedicine Reports)
Introduction: Increased use of telehealth technology during the COVID-19 pandemic helped reduce the impact of some barriers to health care access (e.g., geographical distance) while amplifying the negative impact of others (e.g., poor internet availability). This quality improvement project evaluated a program established at a specialized hospital for children and adolescents with neurodevelopmental disabilities to improve access of patients and families to technologies necessary for telehealth-based care. Methods: Our telehealth access and device distribution program utilized Federal Communications Commission funding to distribute 336 iPads and 279 Wi-Fi hotspots to 414 patients recommended for the program by their clinicians. An average of 1.6 years later, participants received a satisfaction survey via text or email. Results: The referred patient cohort had higher economic disadvantage (average Area Deprivation Index = 7.67) and more language diversity (16% Spanish) compared with hospital averages. About 27% (n = 112) of caregivers completed the satisfaction survey. Most respondents, including 92% of Spanish speakers, reported receiving instructions in their preferred language. Approximately 80% of caregivers stated that the devices enabled telehealth visits. Notably, device abandonment/disuse was considerable, with only 63% of iPads and 36% of Wi-Fi hotspots still in use an average of 1.6 years after device distribution. Discussion: Program efforts were largely successful in facilitating telehealth access via the dissemination of iPads and Wi-Fi hotspots to a patient subpopulation with economic disadvantage and language differences. Follow-up feedback from participants suggests that additional check-ins and device monitoring may be necessary to prevent device abandonment/disuse and maintain longevity of telehealth access.